Development of porous-ceramic hydrostatic bearings - Durazo-Cardenas, Isidro (Cranfield University, 2003)
Porous-ceramic hydrostatic bearings have been recently developed. These bearings have demonstrated an exceptional overall performance when compared with conventional technology bearings. However, despite all the benefits, porous-ceramic hydrostatic bearings have yet to find widespread acceptance due to the problems found in tailoring the bearings geometry and size to suit precision engineering applications, while producing porous-structures with consistent and reproducible permeability. Using a series of fine grades of alumina powders in combination with maize starch granules, a new method for the manufacture of porous-ceramic bearings has been developed, based on the starch consolidation technique. By employing this method, it has been demonstrated that is possible to manufacture bearings of different geometries and shapes, with consistent and reproducible properties. The new method also proved to be low cost and environmentally sound. The performance of the new journal bearings has been investigated in a highly instrumented test-rig, and a comparable performance to that of previous porous- ceramic journal research has been observed. In a direct performance comparison between a porous-ceramic hydrostatic journal bearing and a conventional hydrostatic bearing of the same size, the porous-ceramic bearing demonstrated a significant performance improvement in terms of stiffness, power consumption and thermal performance. In previous research, water lubrication proved to significantly improve the spindle thermal performance. However, water lubrication is feared to promote corrosion within the spindle components. In the present research, the effects of water lubrication in porous-ceramic bearing systems were investigated. As a result, it has been demonstrated that corrosion in typical machine-tool materials can be effectively controlled by using inhibitors and low cost surface coatings. On the other hand, it has been also demonstrated that undesirable foaming, air entrainment and microbial growth can potentially develop in water/inhibitors lubrication systems. In this sense, the use of low viscosity oils proved to offer a comparable performance.